Lamellar organization of pigments in chlorosomes, the light harvesting complexes of green photosynthetic bacteria - Psencík, J; Ikonen, T P; Laurinmäki, P; Merckel, M C; Butcher, S J; Serimaa, R E; Tuma, R (Biophysical journal, 2004)
Chlorosomes of green photosynthetic bacteria constitute the most efficient light harvesting complexes found in nature. In addition, the chlorosome is the only known photosynthetic system where the majority of pigments (BChl) is not organized in pigment-protein complexes but instead is assembled into aggregates. Because of the unusual organization, the chlorosome structure has not been resolved and only models, in which BChl pigments were organized into large rods, were proposed on the basis of freeze-fracture electron microscopy and spectroscopic constraints. We have obtained the first high-resolution images of chlorosomes from the green sulfur bacterium Chlorobium tepidum by cryoelectron microscopy. Cryoelectron microscopy images revealed dense striations approximately 20 A apart. X-ray scattering from chlorosomes exhibited a feature with the same approximately 20 A spacing. No evidence for the rod models was obtained. The observed spacing and tilt-series cryoelectron microscopy projections are compatible with a lamellar model, in which BChl molecules aggregate into semicrystalline lateral arrays. The diffraction data further indicate that arrays are built from BChl dimers. The arrays form undulating lamellae, which, in turn, are held together by interdigitated esterifying alcohol tails, carotenoids, and lipids. The lamellar model is consistent with earlier spectroscopic data and provides insight into chlorosome self-assembly.
Keywords: Bacterial Chromatophores; velikost částic; biologické pigmenty; Pigments, Biological; světlosběrné proteinové komplexy; Cryoelectron Microscopy; Molecular Conformation; elektronová kryomikroskopie; Light-Harvesting Protein Complexes; molekulární konformace; Particle Size; Chlorobium; bakteriální chromatofory